Privacy: Defending an Illusion - Dowding, Martin (Rowman & Littlefield Publishers, 2011)
Matters of privacy have profoundly changed since electronic storage of information has become the norm. Consequently, policy-makers and legislators are trying to keep up with privacy challenges in the workplace, in healthcare, in surveillance, and on social networking sites. With Privacy: Defending an Illusion, Martin Dowding fills a very important gap in policy analysis and the teaching of privacy issues at the senior undergraduate and early graduate student level. In the first section of this book, Dowding recounts historical interpretations of privacy in a wide variety of socio-cultural circumstances. In the second section, the author addresses how information and communication technologies have changed our conceptions about privacy and redirected our focus from keeping information private to sharing it with many more people than we would have even a few years ago. Dowding also examines a variety of possible options for the future of privacy. The appendixes include seminal readings on relevant topics that should encourage debates about the nature of privacy and its problems. Overall, this book provides a solid background for defining and understanding privacy in a wide variety of contexts.